ANALISIS ORNAMEN KERAJINAN GOLOK GALONGGONG DI DESA CILANGKAP, KECAMATAN MANONJAYA, KABUPATEN TASIKMALAYA - Rin Rin agustin; Wan Ridwan Husen; Arni Apriani (Prodi Pendidikan Sendratasik FKIP UMTAS, 2021)
“Galonggong Golok craft is hereditary craft from Galonggong village of Tasikmalaya that still maintains the characteristic shape since a long time. Besides functioning as daily tools necessities, Galonggong golok has a high artistic value. Especially on the handle part, or in Sunda it called as Peurah. So that, there are many buyers interested and make Galonggong golok as decorations and decorative objects. This research is discussed about Golok-making process as well as knowing and understanding of aesthetic visualization in terms of shape and decoration in Cilangkap village, Manonjaya, Tasikmalaya city. The method used is qualitative method since it is more effective to presents the nature of the relationship between the researcher and the subject directly. The data collection techniques used were direct observation, interview and documentation study techniques”.